Cytokine secretion from mononuclear cells cultured in vitro with starch-based polymers and poly-L-lactide - Marques, A. P. (2004)
The cytokine network is one of the major controlling systems of the inflammatory process, driving the magnitude and duration of the host response against invading microorganisms, foreign materials, or altered internal stimuli. Pro- and antiinflammatory cytokines were quantified after in vitro culture of a mixed population of monocytes/macrophages and lymphocytes with biodegradable polymers. Different blends of starch-based polymers and their composites filled with hydroxyapatite were studied and compared with poly-L-lactide. Interleukin (IL)-1, IL-6, and tumour necrosis factor- were investigated as the markers of immunological reactivity because they are known to act at the early stages of injury/invasion. Interferon-, recognized as a proinflammatory cytokine, although not present during early responses was also investigated. Contrarily, IL-4 derived from T lymphocytes, was investigated because it is an immunoregulator that counteracts some aspects of inflammation. T lymphocyte activation was also determined by quantifying IL-2. The results support the hypothesis that different biodegradable polymers can affect mononuclear cell activation and the production of several cytokines associated with the inflammatory process. No IL-2 or interferon- was found in the culture supernatants after 3, 7, and 14 days in the presence of any of the materials. IL-6 was detected in the highest amounts, for all the conditions, followed by tumour necrosis factor-. IL-1 was produced in very low amounts, being undetectable with some of the starch-based materials. IL-4 was the only cytokine that did not demonstrate any significant difference within this group of materials. Starch-based polymers and composites induced lower production of proinflammatory cytokines in comparison to poly-L-lactide.